2006
DOI: 10.1037/0096-1523.32.1.59
|View full text |Cite
|
Sign up to set email alerts
|

When is search for a static target among dynamic distractors efficient?

Abstract: Intuitively, dynamic visual stimuli, such as moving objects or flashing lights, attract attention. Visual search tasks have revealed that dynamic targets among static distractors can indeed efficiently guide attention. The present study shows that the reverse case, a static target among dynamic distractors, allows for relatively efficient selection in certain but not all cases. A static target was relatively efficiently found among distractors that featured apparent motion, corroborating earlier findings. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 70 publications
5
37
2
4
Order By: Relevance
“…Importantly, the item simply has to be unique in some respect, such as being the only stationary item in the field. This hypothesis seems plausible in light of work by Pinto et al (2006) who found that a static item can be efficiently searched for if it was unique in the field of homogenously blinking items.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Importantly, the item simply has to be unique in some respect, such as being the only stationary item in the field. This hypothesis seems plausible in light of work by Pinto et al (2006) who found that a static item can be efficiently searched for if it was unique in the field of homogenously blinking items.…”
Section: Introductionmentioning
confidence: 94%
“…The results showed that within this more complex and dynamic search task both a unique blinking item and a unique moving item captured attention. However, in contrast to Pinto et al (2006) a unique static item did not capture attention. The results favoured the unique feature hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The work by Fahle and Koch (1995) has already been mentioned. More recently, Pinto, Olivers, and Theeuwes (2006) presented participants with a search task in which participants had to detect a static target among randomly (i.e., nonsynchronously) blinking or moving distractors. Participants could do so efficiently, which may imply that the nonsynchronous elements were rejected together.…”
Section: How Are Temporal Groups Detected?mentioning
confidence: 99%